Proceedings of Human Language Technologies: The 2009 Annual Conference of the North American Chapter of the Association for Com 2009
DOI: 10.3115/1620754.1620849
|View full text |Cite
|
Sign up to set email alerts
|

Linear complexity context-free parsing pipelines via chart constraints

Abstract: In this paper, we extend methods from Roark and Hollingshead (2008) for reducing the worst-case complexity of a context-free parsing pipeline via hard constraints derived from finite-state tagging pre-processing. Methods from our previous paper achieved quadratic worst-case complexity. We prove here that alternate methods for choosing constraints can achieve either linear or O(N log 2 N) complexity. These worst-case bounds on processing are demonstrated to be achieved without reducing the parsing accuracy, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…Parser LR LP F1 SINGLE Charniak (2000) 79.6 82.1 80.8 Bikel (2004) 79.3 82.0 80.6 Zhu et al (2013) 81.9 84.3 83.2 Wang et al (2015) 83.2 Our Baseline 81.9 84.4 83.2 Petrov and Klein (2007) 81.9 84.8 83.3 Watanabe and Sumita (2015) 84.3 Roark and Hollingshead (2009) Zhu et al (2013) 84.4 86.8 85.6 Wang et al (2015) 86.6…”
Section: Typementioning
confidence: 95%
See 2 more Smart Citations
“…Parser LR LP F1 SINGLE Charniak (2000) 79.6 82.1 80.8 Bikel (2004) 79.3 82.0 80.6 Zhu et al (2013) 81.9 84.3 83.2 Wang et al (2015) 83.2 Our Baseline 81.9 84.4 83.2 Petrov and Klein (2007) 81.9 84.8 83.3 Watanabe and Sumita (2015) 84.3 Roark and Hollingshead (2009) Zhu et al (2013) 84.4 86.8 85.6 Wang et al (2015) 86.6…”
Section: Typementioning
confidence: 95%
“…To get semi‐supervised features, we first parse unlabeled data with our baseline parser, and then extract two lists from auto‐parsed data, based on which semi‐supervised features are designed. To the best of our knowledge, previous work on boundary prediction (Roark and Hollingshead ; Bodenstab et al ) does not consider semi‐supervised features.…”
Section: Capturing Constituent Boundary Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first, recently graduated PhD student Kristy Hollingshead (now a post-doctoral fellow at the University of Maryland in College Park) collaborated with the PI and graduate student Nate Bodenstab on methods for using a finite-state tagger to achieve complexity improvements in context-free parsing pipelines. First, in 2009, Roark and Hollingshead [2] presented a method to guarantee linear complexity of context-free parsing pipelines given finite-state annotations, as well as related methods that provide large typical case speedups. Recent follow up work [3] showed that additional finite-state tagged constraints can yield further typical case speedups.…”
Section: Comparison Of Actual Accomplishments With the Goals And mentioning
confidence: 99%
“…Recent years have seen a flurry of innovative techniques designed to tackle this problem. These include cube pruning (Chiang, 2007), cube growing (Huang and Chiang, 2007), early pruning (Moore and Quirk, 2007), closing spans (Roark and Hollingshead, 2008;Roark and Hollingshead, 2009), coarse-to-fine methods (Petrov et al, 2008), pervasive laziness (Pust and Knight, 2009), and many more.…”
Section: Introductionmentioning
confidence: 99%